Synthesis and reactivity of an anionic allenylidene complex. Issue 5 (12th January 2018) - Hill, Anthony F.; Manzano, Richard A.
Abstract : The reaction of [W(CCCSiMe3 )(CO)2 (Tp*)] (Tp* = hydrotris(dimethylpyrazolyl)borate) with MeLi generates the first example of an anionic allenylidene complex Li[W(CCCMeSiMe3 )(CO)2 (Tp*)] which reacts with electrophiles (H +, Me + ) at the β-carbon to afford vinylcarbyne complexes and with bromine via oxidative C–C coupling at the β-carbon. Abstract : The reaction of [W(CCCSiMe3 )(CO)2 (Tp*)] (Tp* = hydrotris(dimethylpyrazolyl)borate) with MeLi generates the first example of an anionic allenylidene complex Li[W(CCCMeSiMe3 )(CO)2 (Tp*)] which reacts with electrophiles (H +, Me + ) at the β-carbon to afford vinylcarbyne (allylidyne) complexes [W(CCECMeSiMe3 )(CO)2 (Tp*)] (E = H, Me), and with bromine provides the unprecedented binuclear bis(carbyne) complex {C(CMeSiMe3 )CW(CO)2 (Tp*)}2 via oxidative C–C coupling at the β-carbon.